2018
DOI: 10.1002/mnfr.201800033
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus fermentum Improves Tacrolimus‐Induced Hypertension by Restoring Vascular Redox State and Improving eNOS Coupling

Abstract: LC40 treatment prevents hypertension and endothelial dysfunction induced by tacrolimus by inhibiting gut dysbiosis. These effects are associated with a reduction in vascular oxidative stress, mainly through NOX2 downregulation and prevention of eNOS uncoupling, and inflammation possibly because of decreased Th17 and increased Treg cells polarization in mesenteric lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 59 publications
3
85
0
1
Order By: Relevance
“…Changes in bacteria composition associated with hypertension are followed by alterations in the levels of bacterial metabolic products (Kim, et al, 2018). This concept is corroborated by data from several studies in hypertensive models that demonstrated higher F/B ratio in affected hosts (Yang, et al, 2015;Marques, et al, 2017;Toral, et al, 2018). Furthermore, fibre-rich diets or magnesium acetate and oral minocycline supplementation could restore gut microbiota homeostasis, reduce the F/B ratio and attenuate BP levels (Yang, et al, 2015;Marques, et al, 2017).…”
Section: Hypertensionmentioning
confidence: 73%
“…Changes in bacteria composition associated with hypertension are followed by alterations in the levels of bacterial metabolic products (Kim, et al, 2018). This concept is corroborated by data from several studies in hypertensive models that demonstrated higher F/B ratio in affected hosts (Yang, et al, 2015;Marques, et al, 2017;Toral, et al, 2018). Furthermore, fibre-rich diets or magnesium acetate and oral minocycline supplementation could restore gut microbiota homeostasis, reduce the F/B ratio and attenuate BP levels (Yang, et al, 2015;Marques, et al, 2017).…”
Section: Hypertensionmentioning
confidence: 73%
“…Descending thoracic aortic rings were resected from the animals and were suspended in a wire myograph (model 610M; Danish Myo Technology, Hinnerup, Denmark) for isometric tension measurement as previously described (22). The organ chamber was filled with Krebs solution (composition in mM: 118 NaCl, 4.75 KCl, 25 NaHCO 3 , 1.2 MgSO 4 , 2 CaCl 2 , 1.2 KH 2 PO 4 , and 11 glucose) at 37°C and gassed with 95% O 2 and 5% CO 2 (pH ;7.4).…”
Section: Vascular Reactivity Studiesmentioning
confidence: 99%
“…The lymphocytes and splenocytes were then fixed, permeabilized, and intracellular staining was conducted with mAbs anti-FoxP3 (PE, clone FJK-16s; Thermo Fisher Scientific), anti-IL-17a (PE-Cy7, clone eBio17B7; Thermo Fisher Scientific), and anti-IFN-g (Alexa Fluor 488, clone XMG1.2; Thermo Fisher Scientific) for 30 min at 4°C in the dark. Data collection was performed using a flow cytometer Canto II (BD Biosciences) as previously described (16,22). Supplemental Figure S1 illustrates the gating strategy that was applied.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The probiotic kefir also improved endothelial dysfunction in spontaneously hypertensive rats by decreasing ROS production, increasing NO bioavailability and restoring the recruitment of endothelial progenitor cells . Similarly, Lactobacillus fermentum improved tacrolimus‐induced endothelial dysfunction by reducing vascular oxidative stress and inflammation . The beneficial actions of probiotics on endothelial dysfunction has also been seen in some human studies .…”
Section: Probiotics and Endothelial Dysfunctionmentioning
confidence: 99%